KETERAMPILAN GERAK TARI KREASI DENGAN PENDEKATAN QUANTUM TEACHING DI SEKOLAH DASAR - Aprilianti, Fitri; Marzuki, Marzuki; Utami, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to know and to describe learning problems of Dance subject at elementary school. The lack of teacherâ€™s understanding and the lack of infrastructure become the inhibition of studentsâ€™ creativity to acquire the materials of dance subject. That being said, this research objective is to describe the creative dance movement skill by applying Quantum Teaching approach on Grade IV at elementary school of 36 Sungai Ambawang. The research findings showed that the application of Quantum Teaching approach on creative dance movement on Grade IV at elementary school of 36 Sungai Ambawang succeeded, and it was matching well with the learning objectives. The results were observed when the students demonstrated creative dance movements. The students who previously were unenthusiastic became enthusiastic after they were placed in groups.Â Keywords: Influence, cooperative learning model of talking stick, Learning Outcomes.